Correlation between the nanomechanical characteristic and the phase transformation of BCC-based high entropy alloys produced via powder metallurgy - Lee, Hansung; Sharma, Ashutosh; Kim, Minsu; Ahn, Byungmin (Powder Metallurgy, 2023)
In this study, the effects of Cu addition on AlFeMnTiSi0.75Cu x (x = 0, 0.25, 0.5, 0.75, 1.00; in molar ratios) high entropy alloys (HEAs) prepared via mechanical alloying and spark plasma sintering were investigated. The structure, phase, morphology and composition of HEA powders were analysed and the results revealed that the AlFeMnTiSi0.75Cu x HEAs exhibited a multiphase structure. Additionally, after sintering at 900 °C, the formation of BCC, µ and L21 phases in the densified HEAs was enhanced. The investigation of the hardness, nanoindentation and compressive properties revealed that the microstructural and mechanical properties of AlFeMnTiSi0.75Cu x HEAs were improved at the optimal Cu fraction (0.25 molar ratio). The nanoindentation results revealed that the AlFeMnTiSi0.75Cu x HEAs exhibited the highest hardness and elastic modulus (HIT = 19.2 GPa, EIT = 336 GPa). These results improve the current understanding of multiphase HEAs and may pave way for the development of advanced HEAs with superior mechanical properties.
Keywords: Compression; Cu addition; High entropy alloys; Molar ratio; Multiphases; Nano indentation; Nanomechanical; Phases transformation; Spark-plasma-sintering; Thermodynamic parameter; compression; High entropy alloy; mechanical alloying; multiphase; nanoindentation; thermodynamic parameter